Development of an embryotoxicity test for Enchytraeus crypticus – The effect of Cd. (November 2015) - Gonçalves, Micael F.M.; Bicho, Rita C.; Rêma, Alexandra; Soares, Amadeu M.V.M.; Faustino, Augusto M.R.; Amorim, Mónica J.B.
Abstract : Graphical abstract: Highlights: Embryotoxicity test is proposed for the first time to a soil oligochaete E. crypticus . Embryotoxicity test is short, sensitive and provides mechanistic understanding. Immunohistochemistry indicated competitive binding between Cd and Ca via Ca-channels. Cd (⩾16 mg Cd/kg) caused embryogenesis disruption (non-hatching cocoons). Abstract: The existing standard enchytraeid reproduction test (ERT) concerns the assessment of effects on survival and reproduction. In the present study we optimized and propose an embryotoxicity test using Enchytraeus crypticus. Cadmium (Cd) was used as a test substance. Endpoints evaluated were embryo development, number of embryonic structures, Calcium (Ca) channels quantification and hatching success with macroscopic monitoring, histological and immunohistochemistry analysis. Results showed that Cd is embryotoxic for this species, causing a decrease in the hatching success (EC50  = 3.1 mg/kg), a delay or disruption in formation of embryonic structures depending on concentrations (<5 mg Cd/kg or ⩾16 mg Cd/kg). Results from immunohistochemistry suggest a competitive binding between Cd and Ca for Ca channels, resulting in changes in Ca homeostasis. The use of the E. crypticus embryotoxicity test with the combination of histological and immunohistological tools provided a good option towards mechanistic information enhancing the importance of these tests to evaluate the hazard of chemicals and possible use in risk assessment.